Efforts to Improve the Ability to Run Short Distance 60 Meters Using Traditional Games - Mukhtarom, Akhmad Aliffudin; Prasetyo, Guntum Budi (Bravo's : Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2023)
This study aims to improve students' ability in learning to run a short distance of 60 meters short-distance running using traditional games in Grade VIII-C students of SMPN 1 Kutorejo Mojokerto for the 2022/2023 school year. This research adopts the Classroom Action Research (CAR) methodology. The study involves 32 students from Grade VIII-C of SMPN 1 Kutorejo Mojokerto, comprising 18 male and 14 female students. Data collection methods include observation and 60-meter short-distance running tests. The data analysis technique utilizes a quantitative approach by analyzing the percentage of observations, test results, and the classical completeness of students based on the Minimum Completeness Criteria (KKM). The results indicate that the application of traditional game methods effectively improves the ability of students to run short distances of 60 meters in Class VIII-C of SMPN 1 Kutorejo. In the first cycle, the research achieved a classical completeness rate of 68.75%. This rate increased to 81.25% in the second cycle. The improvement in the ability to run short distances from the pre-cycle to the second cycle was 28,12%.